The Influence of Islamic Religious Education Teachers’ Interpersonal Communication Style on Students’ Discipline and Religious devotion Levels - Jannah, S. Fathiyatul; Sunandar, Dadan; Anshori, Irfan; Romadan, Ade Imun; Kurniawan, Cecep Soleh (STAI Publisistik Thawalib Jakarta, 2024)
Student discipline is influenced by internal factors, environment, religiosity, and effective teacher interpersonal communication, which fosters motivation, role modeling, and supports the development of students' character and spirituality. This study aims to determine the influence of Islamic Religious Education (IRE) teachers’ interpersonal communication style on students' discipline and religious devotion, both simultaneously and partially. This quantitative research used total sampling involving 60 students, with data collected through a Likert-scale questionnaire and analyzed using descriptive statistics, classical assumption tests, validity, reliability, MANOVA, and t-tests. The analysis results show that teacher interpersonal communication significantly influences student discipline and religious devotion, with a contribution of 78.9%, while 21.1% is influenced by other factors. Based on the t-test (R²), the effect on discipline was 44.13%, while on religious devotion it was 23.45%. Conclusion: positive interpersonal communication also strengthens students' character and internalization of spiritual values through interactions with religious education teachers.